Bilateral Bone Ridge Splitting in Maxilla with Immediate Implant Placement in a Patient with Osteoporosis: A Clinical Report with 2-Year Follow-up - Rafał Flieger (Hindawi Limited, 2019)
Every year, a higher percentage of bisphosphonates is prescribed for osteoporosis treatment which can lead to bone osteonecrosis after several surgical procedures in the oral cavity. This report describes an approach to restore two missing teeth, employing bilateral bone ridge splitting in the maxilla with immediate placement of implants in a patient using bisphosphonates in the management of osteoporosis. Two titanium implants with a width of 3.45 mm and a length of 10 mm were placed in the maxillary ridge with a diameter of 4.4 mm and 3.0 mm in positions 15 and 24 according to the classification of the World Dental Federation. The implants were placed immediately by bone splitting, using a piezosurgery device and guided bone regeneration with an alloplastic material and a collagen membrane. Five months later, the implants were uncovered and the final porcelain crowns were cemented. 24 months later, the control through clinical and radiographical examinations showed no bone loss in the collar part of the implants and the proper status of the peri-implant soft tissue without any signs of inflammation. Piezosurgery is a useful and safe method of ridge splitting in a very thin ridge (4.5 and 3.0 mm).